Arrhenius Plot Analysis, Temperature Coefficient and Q10 Value Estimation for the Effect of Temperature on the Rate of Molybdenum Reduction by Serratia marcescens strain DRY6 - Abubakar, Aisami (Journal of Environmental Microbiology and Toxicology, 2021)
Molybdenum is a micronutrient that serves as a co-factor for over 50 enzymes and catalyses a variety of hydroxylation and redox transfer activities in animal and plant physiology. When its concentration is elevated, it poses a great danger as it can interfere with the processes of spermatogenesis and oogenesis in several animals including fish. Its remediation using molybdenum-reducing bacterium is an emerging important tool. One of the parameters that are important in governing molybdenum reduction is temperature. Several models may be used to simulate the growth rate of microorganisms on various media as a function of temperature. Arrhenius is one of the very popular models since it has minimal parameters. Temperature generally affects microbial growth and metabolic activity on their substrates. The small nature of microbes makes them susceptible to change in the surrounding temperature. Growth on molybdenum by Serratia marcescens strain DRY6 is described, with a discontinuous chevron-like graph of apparent activation energy with a breakpoint at 26.25 oC. Regression analysis resulted in two activation energies: 15-25 oC and 30–40 oC with the activation energies of 52.7 kJ/mol and 13.33 kJ/mol, respectively. For the examined temperature range (15-25 oC), a Q10 value of 2.08 and a theta value of 1.02 was calculated. This is study is very useful in predicting the breakdown of molybdenum and the movement of molybdenum during bioremediation.